Proposed solutions for marine debris in the Windward Islands- perspectives from key policy makers and policy influencers - Roxanne E. D. Graham; Roxanne E. D. Graham (Frontiers in Marine Science, 2023)
With the rise of regionalization and globalized approaches to dealing with the associated sources and impacts of marine debris, it is often a challenge to properly capture the unique context and special needs of small island developing states (SIDS) worldwide. In the SIDS context, locals’ perspectives should have a voice in scientific research, as well as in devising potential solutions, at all and different scales. With the view to tailor solutions for the prevention, reduction and mitigation of marine debris, this research explores the professional opinion of local knowledge holders including policy makers from government organizations (GOs) and key policy influencers in non-governmental organizations (NGOs) in the five English-Speaking Windward Islands of the Eastern Caribbean. To achieve that objective, surveys were conducted with these two groups in Barbados, Dominica, Grenada, St. Lucia and St. Vincent and the Grenadines. On the causes of the debris problem, the survey revealed that the lack of a proper waste management systems on islands, recycling limitations and inappropriate disposal behaviors of the population are generally thought to be the main contributory factors to the accelerating problem of marine debris. Further, phenomena such as Sargassum influxes, sea level rise and extreme weather events exacerbate the problem including most especially tropical storms and hurricanes. On the recommended solutions, over eighty percent of the participants identified monitoring and policing services as a main constraint that prohibits sound coastal and marine litter handling. Ninety-five percent identified establishing feasible recycling systems and sixty-seven percent identified changing social behaviors (including a combination of product and consumer literacy, disposal habits, compliance with laws and regulations) as national priorities for enabling on-the-ground actions for better coastal and marine litter prevention and reduction going forward. These findings reinforce recently published work which indicates the need for effective solid waste management systems in the Eastern Caribbean for cleaner and healthier oceans. An additional recommendation was proposed to address a major source of the marine litter problem- upstream producers. Furthermore, given the natural events component, this research proposes incorporating the Sendai Framework for disaster risk reduction in future proposed mitigation measures with a view to building the resilience of SIDS and local communities in combating the impacts of marine debris.